عمالة الأطفال وأثرها على المجتمع - عقيل, أديب; الزبيدي, بسمة (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
The research aims to shed light on the phenomenon of child labor, because of its great importance, and to eliminate the negative effects of this phenomenon.Researcher proceeded to explain the underlying causes of child labor, and the problems caused by this phenomenon, and their implications to the child.The research sample selection is my intention because of the lack of working children in a specific place and stationed in different places where amounted to 20 children ages ranged from 12-15 years old.The study showed the underlying causes of this phenomenon, the study recommended a set of recommendations that would reduce this phenomenon.يهدف البحث لإلقاء الضوء على ظاهرة عمالة الأطفال ، لما لها من أهمية كبيرة، والقضاء على الآثار السلبية الناجمة عن هذه الظاهرة.عمدت الباحثة إلى توضيح الأسباب الكامنة وراء عمالة الأطفال، والمشكلات الناجمة عن هذه الظاهرة، والآثار المترتبة عليها تجاه الطفل.تم اختيار عينة البحث بشكل قصدي بسبب عدم وجود الأطفال العاملين في مكان محدد وتمركزهم في أماكن مختلفة حيث بلغت 20 طفلاً تراوحت أعمارهم ما بين 12 – 15 سنة.وبينت الدراسة الأسباب الكامنة وراء هذه الظاهرة، وأوصت الدراسة مجموعة من التوصيات التي من شأنها الحد من هذه الظاهرة.